2022
DOI: 10.3390/plants11131653
|View full text |Cite
|
Sign up to set email alerts
|

OsMLP423 Is a Positive Regulator of Tolerance to Drought and Salt Stresses in Rice

Abstract: Rice (Oryza sativa L.) is one of the main food crops for human survival, and its yield is often restricted by abiotic stresses. Drought and soil salinity are among the most damaging abiotic stresses affecting today’s agriculture. Given the importance of abscisic acid (ABA) in plant growth and abiotic stress responses, it is very important to identify new genes involved in ABA signal transduction. We screened a drought-inducing gene containing about 158 amino acid residues from the transcriptome library of rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The discovery and characterization of ABREs have provided insight into the molecular mechanisms underlying ABA-mediated stress responses in plants. Studies in the promoter region of the Arabidopsis thaliana RD29A gene and rice OsRab16A gene contains contain one and three functional ABRE respectively, essential for the ABA-mediated induction of RD29A expression in response to dehydration stress and OsRab16A expression in response to salt stress [32,33]. Similar studies in wheat have shown that the promoter region of the wheat TaERF1 gene contains multiple ABREs that are involved in the ABA-mediated induction of TaERF1 expression in response to drought stress [34].…”
Section: Regulation Of Drought Tolerance and Abamentioning
confidence: 89%
“…The discovery and characterization of ABREs have provided insight into the molecular mechanisms underlying ABA-mediated stress responses in plants. Studies in the promoter region of the Arabidopsis thaliana RD29A gene and rice OsRab16A gene contains contain one and three functional ABRE respectively, essential for the ABA-mediated induction of RD29A expression in response to dehydration stress and OsRab16A expression in response to salt stress [32,33]. Similar studies in wheat have shown that the promoter region of the wheat TaERF1 gene contains multiple ABREs that are involved in the ABA-mediated induction of TaERF1 expression in response to drought stress [34].…”
Section: Regulation Of Drought Tolerance and Abamentioning
confidence: 89%
“…Improving the antioxidant activity to reduce the over-production of ROS is the most useful way to enhance the stress tolerance in plants (Panda et al 2021 ), such as enhancing the activity of the POD and SOD (Gill and Tuteja 2010 ). Overexpression of OsMLP423 or OsSCL30 both reduced the damage caused by ROS through enhancing the activities of SOD and POD (Zhou et al 2022 ; Zhang et al 2022 ). Our result showed that overexpression of OsHAD3 could increase the over-accumulation of ROS but antisense-expression lines were opposite under drought stress condition, which could be further confirmed by the staining results of DAB and NBT and transcription level of genes, OsRbohA and OsRbohE .…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic activity ceased by the extreme rolling of the leaves which is considered to not play a positive role in the other beneficial process in the plant. Therefore, the rolling approach of the leaves is the most critical process for the perfect functioning of the plants [72]. Bulliform cells are an example of a vital strategy to water conservation and photosynthesis enhancement.…”
Section: Is Leaf Rolling Necessary In Plants?mentioning
confidence: 99%